To flap or not to flap: comparison between flapping and clapping propulsions. (7th June 2017) - Martin, Nathan; Roh, Chris; Idrees, Suhail; Gharib, Morteza
Abstract : A comparison between swimming by flapping and by periodic contractions is conducted. Swimming by flapping is approximated as a pitching plate while swimming by periodic contractions is approximated as clapping plates. A direct comparison is made between the two propulsion mechanisms by utilizing a machine that can operate in either a flapping or a clapping mode between Reynolds numbers of 1880 and 11 260 based on the average plate tip velocity and span. The average thrust generated and the average input power required per cycle are compared between cases where the total sweep angle and the total sweep time are identical. Variation of the kinematics results in a similar thrust between the two mechanisms, but a greater power is required for clapping. Variation of the flexibility results in a consistent decrease in the required power for clapping and a decrease in thrust at high flexibility. Variation of the duty cycle for clapping rigid plates results in a significant increase in thrust and a significant decrease in the required power. Overall, the results suggest that flapping propulsion is the more effective propulsion mechanism within the range of Reynolds numbers tested.